Integrated Gene Co-expression Analysis and Metabolites Profiling Highlight the Important Role of ZmHIR3 in Maize Resistance to Gibberella Stalk Rot - Sun, Yali; Ruan, Xinsen; Wang, Qing; Zhou, Yu; Wang, Fang; Ma, Liang; Wang, Zhenhua; Gao, Xiquan (Frontiers in Plant Science, 2021)
Gibberella stalk rot (GSR) caused by Fusarium graminearum is one of the most devastating diseases causing significant yield loss of maize, and GSR resistance is a quantitative trait controlled by multiple genes. Although a few QTLs/resistance genes have been identified, the molecular mechanisms underlying GSR resistance remain largely unexplored. To identify potential resistance genes and to better understand the molecular mechanism of GSR resistance, a joint analysis using a comparative transcriptomic and metabolomic approaches was conducted using two inbred lines with contrast GSR resistance, K09 (resistant) and A08 (susceptible) upon infection with F. graminearum. While substantial number of differentially expressed genes (DEGs) associated with various defense-related signaling pathways were identified between two lines, multiple hub genes likely associated with GSR resistance were pinpointed using Weighted Gene Correlation Network Analysis (WGCNA) and K-means clustering. Moreover, a core set of metabolites, including anthocyanins, associated with the hub genes were determined. Among the complex co-expression networks, ZmHIR3 showed strong correlation with multiple key genes, and genetic and histological studies showed that zmhir3 mutant is more susceptible to GSR, accompanied by enhanced cell death in the stem in response to infection with F. graminearum. Taken together, our study identified differentially expressed key genes and metabolites, as well as co-expression networks associated with distinct infection stages of F. graminearum. Moreover, ZmHIR3 likely plays a positive role in disease resistance to GSR, probably through the transcriptional regulation of key genes, functional metabolites, and the control of cell death.